Stress and Coping among Black Women Employed in Non-professional Service and Professional Occupations in Florida and Georgia. (3rd August 2015) - Gary, Faye A.; Yarandi, Hossein; Hassan, Mona
Abstract : Culture enhances the ability to address the stressors related to ethnicity/race, employment, and lifestyle. From this interaction, two coping patterns emerge: individualist-oriented or collectivist-oriented, of which women prefer the latter. However, there is limited knowledge about the impact of ethnicity/race on the coping strategies of Black working women in the USA. Therefore, the purpose of this cross-sectional survey was to examine the coping strategies of two groups of Black women, those who work in non-professional service-related jobs and those employed as professionals. We explored Black women from two southern states, Florida and Georgia, in their use of coping strategies for everyday stressors. A modified version of Lazarus and Folkman's Transactional Model was used as the framework of this study. The sample for this cross-sectional survey consisted of 313 Black women employed in non-professional service jobs and 343 in professional roles. The thoughts and actions related to coping in everyday stressors were measured with The Ways of Coping Questionnaire.